1991
DOI: 10.1079/bjn19910023
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and endocrinological manipulation of lean deposition in forage-fed steers

Abstract: The effect of supplementing grass silage with fishmeal on growth, muscle composition and the rate of muscle protein synthesis was investigated in young Friesian steers with and without oestradiol implants. The effect of the P-adrenergic agonist cimaterol was simultaneously investigated in animals fed on silage alone. Treatments lasted for 9 or 10 weeks. Fishmeal supplementation significantly increased animal growth rates (P < 0.001) and the weights of three dissected muscles (P < 0.001) compared with the silag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
3
14
1
1
Order By: Relevance
“…Indeed, muscle DNA concentration (pg/g protein) is sometimes less in treated muscles than in control muscles (Kim et al 1987). The predominant mechanism of action of these agents is thus believed to be a reduction in protein degradation, although protein synthesis has also been shown to be stimulated in some studies (Dawson et al 1991). This is supported by the observation that translational efficiency (i.e.…”
Section: Effects On Muscle Jibre Hypertrophysupporting
confidence: 69%
See 2 more Smart Citations
“…Indeed, muscle DNA concentration (pg/g protein) is sometimes less in treated muscles than in control muscles (Kim et al 1987). The predominant mechanism of action of these agents is thus believed to be a reduction in protein degradation, although protein synthesis has also been shown to be stimulated in some studies (Dawson et al 1991). This is supported by the observation that translational efficiency (i.e.…”
Section: Effects On Muscle Jibre Hypertrophysupporting
confidence: 69%
“…the amount of protein synthesized per unit RNA) is increased by Padrenergic agonists . All muscles do not respond equally to treatment with P-adrenergic agonists (Dawson et al 1991) and this is probably related to different fibre-type content of different muscles. The crosssectional area of type I1 (fast-contracting, mixed glycolytic-oxidative) fibres tends to be increased more consistently than type I (slow contracting, oxidative) fibres (see Yang & McElligott, 1989).…”
Section: Effects On Muscle Jibre Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma IGF-1 concentrations were also reduced in these animals compared with animals receiving either treatment alone in agreement with the suggestion of Beermann et al (1987) that IGF-1 concentrations are influenced by insulin secretion rates. It would thus appear that the small additional increase in muscle accretion observed in immunized animals receiving cimaterol was not mediated through the GH-IGF-1 axis, but through an enhancement of the P-agonist effect, p-agonists are believed to increase muscle protein accretion through a reduction in the rate of protein degradation and an increase in the rate of protein synthesis (Dawson et al, 1991b;NRC, 1994). Both processes are regulated separately and alteration in the rate of either process will result in increased protein accretion.…”
Section: Discussionmentioning
confidence: 97%
“…Beta-adrenergic agonists have direct effects on muscle tissue in cattle (Byrem et al, 1998), binding to β2 and β1 receptors located on the tissue, thereby stimulating muscle accretion (Smith et al, 1989) and possibly decreasing protein degradation (Dawson et al, 1988). Byrem et al (1998) observed increases in amino acid uptake by muscle tissue in steers treated with cimaterol, which is associated with the increased protein accretion.…”
Section: Beta-adrenergic Agonistsmentioning
confidence: 99%